Male animal sterilization: history, current practices, and potential methods for replacing castration - Hess, Rex A.; Park, Chan Jin; Soto, Sandra; Reinacher, Lindsey; Oh, Ji-Eun; Bunnell, Mary; Ko, CheMyong J. (Frontiers in Veterinary Science, 2024)
Sterilization and castration have been synonyms for thousands of years. Making an animal sterile meant to render them incapable of producing offspring. Castration or the physical removal of the testes was discovered to be the most simple but reliable method for managing reproduction and sexual behavior in the male. Today there continues to be global utilization of castration in domestic animals. More than six hundred million pigs are castrated every year and surgical removal of testes in dogs and cats is a routine practice in veterinary medicine. However, modern biological research has extended the meaning of sterilization to include methods that spare testis removal and involve a variety of options, from chemical castration and immunocastration to various methods of vasectomy. This review begins with the history of sterilization, showing a direct link between its practice in man and animals. Then it traces the evolution of concepts for inducing sterility, where research has overlapped with basic studies of reproductive hormones and the discovery of testicular toxicants, some of which serve as sterilizing agents in rodent pests. Finally, the most recent efforts to use the immune system and gene editing to block hormonal stimulation of testis function are discussed. As we respond to the crisis of animal overpopulation and strive for better animal welfare, these novel methods provide optimism for replacing surgical castration in some species.